Pengaruh Event Marketing dan Sosial Media Terhadap Minat Beli Pada PT. Nusatara Surya Sakti Kepada Dua Tangerang - Iwan Asmadi; Tri Lestari; Chairudin Chairudin (POLITEKNIK KETENAGAKERJAAN, 2023)
Nusantara Surya Sakti is a company that operates as an official Honda motorbike dealer, Purchase interest is a process between evaluating alternatives and purchasing decisions. This research aims to determine the influence of event marketing and social media on purchasing interest at PT. Nusantara Surya Sakti, Kelapa Dua Tangeran. This type of research uses quantitative research with statistical methods. The data collection method used in this research used a questionnaire distributed to 100 respondents. The accidental sampling technique, the results of this research, shows that the regression equation value Y = 24.744 – 0.0.67X1 + 0.598X2, in part, event marketing and social media have a positive and significant effect on buying interest with an R square value in the determination test of 0.293. So it can be concluded that the influence of event marketing and social media on purchasing interest is 29.3%, while the remaining 70.7% is influenced by other variables outside this research.